2003
DOI: 10.1024/0369-8394.92.37.1515
|View full text |Cite
|
Sign up to set email alerts
|

Effekte der Hüftarthroplastik und der nachfolgenden stationären postoperativen Rehabilitation auf körperliche Funktion und Lebensqualität

Abstract: The aim of the present study was to investigate the effects of hip arthroplasty followed by an inpatient rehabilitation. Moreover, the relationships among functional status, quality of life and satisfaction with life or health status were examined. Patients were assessed before hip arthroplasty, at the start and at the end of the inpatient rehabilitation. Functional status was measured by using the WOMAC questionnaire and quality of life with the Medical Outcome Survey Short Form 36 (SF-36). Satisfaction was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The functional benefit of a comprehensive inpatient rehabilitation programme of 3 weeks is demonstrated nicely by the WOMAC self-assessment questionnaire for pain, stiffness and function. This is in perfect agreement with Rogenmoser et al (39), who found significant improvements in WOMAC score, SF-36 and quality of life after 3 weeks of inpatient rehabilitation. In our study, we documented a significant decrease in the TUG test, a standardized instrument for mobility assessment (26).…”
Section: Discussionsupporting
confidence: 92%
“…The functional benefit of a comprehensive inpatient rehabilitation programme of 3 weeks is demonstrated nicely by the WOMAC self-assessment questionnaire for pain, stiffness and function. This is in perfect agreement with Rogenmoser et al (39), who found significant improvements in WOMAC score, SF-36 and quality of life after 3 weeks of inpatient rehabilitation. In our study, we documented a significant decrease in the TUG test, a standardized instrument for mobility assessment (26).…”
Section: Discussionsupporting
confidence: 92%